2022
DOI: 10.2217/fon-2022-0140
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with poorly differentiated gastric neuroendocrine neoplasms: a multi-center study in China

Abstract: Background: The incidence of poorly differentiated gastric neuroendocrine neoplasms (G-NENs) has been increasing during the past decades. Methods: A total of 183 patients diagnosed with poorly differentiated G-NENs were enrolled from eight hospitals during 2010–2019 in China. All cases included have accepted abdominal surgery in tertiary hospitals. Result: T3 (HR: 2.66, p = 0.019), T4 (HR: 3.62, p = 0.005), stage IV (HR: 5.67, p < 0.001), vascular invasion (HR: 1.59, p = 0.048) were independent risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…31,55,56 Drawing from a comprehensive and thorough comprehension of g-NEC and g-MiNEN, most researchers agree that postoperative adjuvant chemotherapy could offer potential benefits to these patients. 27,[57][58][59][60] However, it is important to note that certain studies have reported the ineffectiveness of adjuvant chemotherapy in treating g-NEC and g-MiNEN, failing to demonstrate significant enhancements in survival outcomes. 61,62 The variations in treatment outcomes can be attributed to several factors, including tumor heterogeneity, drug selection, and population responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,55,56 Drawing from a comprehensive and thorough comprehension of g-NEC and g-MiNEN, most researchers agree that postoperative adjuvant chemotherapy could offer potential benefits to these patients. 27,[57][58][59][60] However, it is important to note that certain studies have reported the ineffectiveness of adjuvant chemotherapy in treating g-NEC and g-MiNEN, failing to demonstrate significant enhancements in survival outcomes. 61,62 The variations in treatment outcomes can be attributed to several factors, including tumor heterogeneity, drug selection, and population responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed surgical resection establishing itself as the most effective therapeutic approach for g‐NEC 31,55,56 . Drawing from a comprehensive and thorough comprehension of g‐NEC and g‐MiNEN, most researchers agree that postoperative adjuvant chemotherapy could offer potential benefits to these patients 27,57–60 . However, it is important to note that certain studies have reported the ineffectiveness of adjuvant chemotherapy in treating g‐NEC and g‐MiNEN, failing to demonstrate significant enhancements in survival outcomes 61,62 .…”
Section: Discussionmentioning
confidence: 99%